PENGARUH PEMBELAJARAN KONTEKSTUAL TERHADAP KEMAMPUAN PEMAHAMAN DAN REPRESENTASI MATEMATIS SISWA SEKOLAH DASAR - Handayani, Hani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2015)
This study aims to determine whether the ability of understanding and reoresentasi mathematical students who get contextual learning is higher than the capability of understanding and the mathematical representation of students who learn by direct instruction, as well as to determine whether the increased ability of comprehension and mathematical representation of students who get contextual learning is higher than increase in students who received direct instruction teaching. This study is a quasi-experimental study design with pretest posttest control group research desaign. Based on data analysis and data posttest scores normalized gain, it can be concluded that 1) the ability of understanding and abilities of students who obtain a mathematical representation of contextual learning is higher than the capability of mathematical understanding of students who received direct instruction; 2) to improve the understanding and ability of students who obtain a mathematical representation of contextual learning is higher than the increase in understanding of mathematical ability of students who received direct instruction